PERENCANAAN STRATEGIS SI/TI PADA DOCUMENT MANAGEMENT MENGGUNAKAN WARD AND PEPPARD (STUDI KASUS: PT. VISIONET DATA INTERNATIONAL) - Agustinus Fritz Wijaya; Vincentius Dhendy Radya Damara (Jurnal Ilmiah Terpadu Universitas Bina Darma, 2020)
PT. Visionet Data International is a company engaged in the field of IT that serves Total IT Managed services. Because the development of Information Systems and Information Technology (IS / IT) in fulfilling the company's vision and mission, a good plan is needed. In this research focuses on the documentation management system in which there is no good company documentation management in accordance with the provisions in force. Regarding data collection methods, this research uses interviews with company’s employees. This research is a qualitative descriptive study using the Ward and Peppard method. Which includes SWOT analysis, Value Chain analysis, PEST analysis, application mapping analysis using McFarlan Strategic Grid and analysis of Proposed Information Systems. This research results in the form of application portfolio recommendations such as the development of Document Management in the form of Web-based applications in which all processes are integrated into one. So in the process of submitting new documents to the process of issuing documents can be done in an application which can support the reduction in the use of paper in the company.